Predictors for and coverage of influenza vaccination among HIV‐positive patients: a cross‐sectional survey. Issue 7 (30th December 2016) - Harrison, N; Poeppl, W; Herkner, H; Tillhof, KD; Grabmeier‐Pfistershammer, K; Rieger, A; Forstner, C; Burgmann, H; Lagler, H
Abstract : Objectives: Influenza vaccination is recommended for HIV‐infected patients, but limited data about vaccination rates are available. The aim of this study was to evaluate the coverage of and predictors for influenza vaccination among HIV‐positive patients. Methods: All HIV‐positive patients who visited the HIV out‐patient department of the University Hospital of Vienna, Austria, between June and August 2015 were asked to participate in this survey by completing a questionnaire. Results: A total of 455 HIV‐positive patients completed a questionnaire, with 359 male and 96 female participants with a mean age of 46 years. The influenza vaccination rate for the previous season (2014/2015) was 11.9% [ n = 54/455; 95% confidence interval (CI) 9.2–15.2%]. Older age was significantly associated with a positive influenza vaccination status. Obtaining information through a medical consultation or receiving a direct recommendation for vaccination by a physician had a significant impact on vaccination behaviour. The probability of being vaccinated against influenza was about 13 times higher among patients who received a recommendation for vaccination by their family physician or by their HIV specialist ( P < 0.001). Important reasons for declining vaccination were fear of side effects (39%), not considering influenza as a severe disease (36%) and reasons related to HIV: 17% were worried that the vaccine could worsen the course of HIV infection and 16% believed vaccination would fail because of their compromised immune system. Conclusions: A low influenza vaccination rate of 11.9% was detected in this HIV‐positive cohort. The most effective impact for a positive vaccination status was direct recommendation of the influenza vaccine by the attending physician.